Research on the Application of Traditional Chinese Artistic Modeling Elements in Animated Character Design - Zhao, Zhuo (Transactions on Social Science, Education and Humanities Research, 2023)
The traditional artistic modeling elements of China are rich and colorful. Their application in animated character design not only highlights the distinctive features of traditional artistic modeling elements but also promotes China’s excellent traditional culture. This paper mainly discusses in detail the measures of applying traditional Chinese artistic modeling elements to animated character design. Animation character designers can pay attention to the reasonable application of traditional Chinese artistic modeling elements against the background of new media, highlighting traditional literature, fine arts, and philosophy in the design process. Only by doing this can diverse artistic forms be reflected through animated characters, making the design more valuable and promoting sustainable development of China’s traditional animation industry.